To share or not to share? That is the (social media) dilemma. Expectant mothers questioning and making sense of performing pregnancy on social media. (April 2021) - Cino, Davide; Formenti, Laura
Posting about one's pregnancy on social media has become a common practice for many expectant mothers in the global North. However, social media sharing implies transcending the conventional time and space boundaries of interpersonal communication. As such, women may feel ill at ease when deciding whether and how to narrate their journey online. This article examines mothers' pre-birth social media dilemmas via a thematic analysis of 1237 posts from 26 threads on a parenting forum in which expectant mothers discussed their doubts and fears about sharing their pregnancy on social media. The dilemmatic dimension of social media sharing challenges the simplistic idea that sharenting is a practice most women naively adhere to without question. Indeed, the present research shows that online posters face dilemmas about performing their pregnancies on social media and collectively learn to make sense of and question a culture of surveillance, while reclaiming their self-representational agency in the process.